Incidence and associated factors of extrauterine growth restriction (EUGR) in preterm infants, a cross-sectional study in selected NICUs in Ethiopia. Issue 1 (12th October 2020) - Gidi, Netsanet Workneh; Goldenberg, Robert L; Nigussie, Assaye K; McClure, Elizabeth; Mekasha, Amha; Worku, Bogale; Siebeck, Matthias; Genzel-Boroviczeny, Orsolya; Muhe, Lulu M
Abstract : Background: Preterm infants have high risk of developing growth restriction and long-term complications. Enteral feeding is often delayed in neonatal intensive care units (NICUs) for the fear of feeding intolerance and the associated necrotising enterocolitis, and recent advances in nutritional support are unavailable in low-income countries. Objective: The aim of this study was to assess the incidence and associated factors of extrauterine growth restriction (EUGR) among preterm infants in selected NICUs in Ethiopia. Method: This was a cross-sectional study involving a subgroup analysis of preterm infants admitted to hospitals, from a multicentre descriptive study of cause of illness and death in preterm infants in Ethiopia, conducted from 2016 to 2018. EUGR was defined as weight at discharge Z-scores <−1.29 for corrected age. Clinical profiles of the infants were analysed for associated factors. SPSS V.23 software was used for analysis with a significance level of 5% and 95% CI. Result: From 436 preterm infants included in the analysis, 223 (51%) were male, 224 (51.4%) very low birth weight (VLBW) and 185 (42.4%) small for gestational age (SGA). The mean (SD) of weight for corrected age Z-score at the time of discharge was −2.5 (1.1). The incidence of EUGR was 86.2%. Infants who were SGA, VLBW and longer hospital stay over 21 days had increased risk of growth restriction (p-value<0.01). SGA infants had a 15-fold higher risk of developing EUGR at the time of discharge from hospital than those who were appropriate or large for gestational age (OR (95% CI)=15.2 (4.6 to 50.1). Conclusion: The majority of the infants had EUGR at the time of discharge from the hospital, which indicates suboptimal nutrition. Revision of national guidelines for preterm infants feeding and improvement in clinical practice is highly required.